(untitled) (Journal of Dhaka Medical College, 2017)
Background: Oral melphalan, prednisone and Thalidomide (MPT) has been tested and proved efficacy in multiple myeloma (MM). But, no data are available on the response rate and adverse effect of oral MPT in diagnosed symptomatic MM patients who are non-transplant candidates in our population and ethnic diversity. Here, we evaluated response rate and adverse effects of MPT. Methods: 16 diagnosed symptomatic MM patients (age range 45-75 years) received MPT (Melphalan 4 mg/m2 divided dose and Prednisone 40 mg/m2 once daily for 7 days every month plus Thalidomide 100 mg/day at night continuously) from January 2010 to December 2011 at department of Hematology, Dhaka medical college and hospital, Dhaka. After 3 courses of MPT, 2 patients had no improvement, so changed to another protocol. Rest 14 patients had completed 6 cycles of MPT and evaluated for both response rate and toxicity. Results: The overall response rate (ORR) was 87.5% (n=14); complete response (CR) rate 50% (n=8), partial response (PR) rate 31.25% (n=5), minimal response (MR) rate 6.25% (n=1) and no response (NR) was 12.50% (n=2) of patients. During MPT therapy, MM patients noticed abdominal discomfort in 31.11% (n=14), insomnia in 17.78% (n=8), constipation in 13.33% (n=6), numbness/ peripheral neuropathy in 13.33% (n=6) and developed infection in 6.67% (n=3) and hyperglycaemia in 4.44% (n=2) of patients. Life threatening complications like DVT were absent. Almost all adverse effects were mild, reversible grade 1/2 toxicity and mostly developed within first cycle of MPT. Treatment related mortality was absent. Conclusions: It clearly reveals MPT induces increase response rate with low cost and minimal side effects which might bring hope to the poor patients of our country. J Dhaka Medical College, Vol. 25, No.1, April, 2016, Page 61-66